Superfood boost : immunity-building smoothie bowls, green drinks, energy bars, and more! - Palmcrantz Aziz, Erica, 1977- (Skyhorse Publishing, 2018)
"Superfood Boost inspires and teaches you to start planning simple and quick dishes to improve your well-being. Developing better habits doesn't have to be difficult or time-consuming. Just replace your snacks with nutrient-rich smoothies and energy bars, and you'll see your health improve in no time at all! Simply put, food is medicine, and superfoods contain maximum nutrition in every serving, giving your body a healthy boost. With this book, you will learn which ingredients to choose to make the most out of your snacks and meals?and they can all be found in a supermarket near you! All of the recipes are based on raw food ingredients and help you get the most nutrition in the best possible way"--Amazon.com.